Axial Loading Behaviour of Self-Compacting Concrete-Filled Thin-Walled Steel Tubular Stub Columns - Yunyang Wang; Lei Xiao; Chu Jiang; Yandong Jia; Guang Yang; Meng Li; Xiangliang Tang; Duo Chen (Advances in Civil Engineering)
This paper presents an experimental investigation on the mechanical behaviour of self-compacting concrete-filled thin-walled steel tubular (SCCFTST) stub columns loaded in axial compression to failure. Four specimens were tested to study the effect of diameter to wall thickness (D/t) ratios on the ultimate load, failure modes, and ductility of the columns. Confinement of the steel tube to concrete was also addressed. The failure modes, load versus displacement curves, and load versus strain curves were examined in detail. The experimental results showed that the ultimate state is reached when severe local buckling and rupture occurred on the steel tubes, and the concrete near the rupture has been crushed. The columns with larger D/t ratios appeared more local buckling, and its location is more close to the end of the columns. The SCCFTST stub columns with smaller D/t ratios show higher ultimate load and better ductility, and the steel tubes can exert higher confinement to the concrete.